Analisis Kinerja Reksa Dana Saham Menggunakan Metode Sharpe, Treynor dan Jensen Dengan IHSG dan Lq45 (Reksa Dana Saham Yang Terdaftar Di OJK Tahun 2009-2013) - Ningsih Pratiwi; Randy Heriyanto (Jurusan Akuntansi Politeknik Negeri Padang, 2017)
Risk and Return are two things that must be considered in measuring portfolio performance, there are three parameters that have accommodated Risk and Return; Sharpe method, Treynor method, and Jensen method. These three performance measurements assume a relationship between portfolio returns, portfolio risks, and returns from several market indices. The measurement of stock portfolio performance can be facilitated by using a bench mark, which is IHSG and LQ 45 shares. The purpose of this study is to determine the performance of stock mutual funds against the CSPI and LQ 45. Penunlis conducted research on 29 conventional equity funds, which fulfilled the selected criteria purposive sampling. From the calculation results, it can be seen that only a number of mutual fund products are able to outperform the IHSG and LQ 45, but no one is able to survive consistently having the best performance during the 2009 to 2013 observation period. This is caused by changes in average returns and beta generated by mutual fund products.